Preparation of Aquilaria microcarpa and Aquilaria beccariana Plant Types at Arboretum Dipterokarpa Forest Ecosystem Research & Development Center, Samarinda, East Kalimantan Province - Hamdi Laiti; Ismail Ismail; Abdul Kholik Hidayah; Ismail B Bakrie (Universitas 17 Agustus 1945 Samarinda, 2019)
In order to support the development of Aquilaria microcarpa and Aquilaria beccariana plants, specifically there is a need for research on the potential of stands in an area by considering the factors that influence the genetic abilities of individual plants that interact with the environment, including: soil or site factors, climate factors , topographic factors, plant species and animal disorders.The aim of this study was to determine the increment of diameter, height and volume of Aquilaria microcarpa and Aquilaria beccariana plant species when the plants were 8 years old in 2014 to eleven years old when the study was conducted, namely in 2017.This study uses Primary Data in the form of diameter and height measurement data that have been analyzed to produce the amount of increment and average, diameter, height and volume of plant species of Aquilaria microcarpa and Aquilaria beccariana determined as many as 50 plant samples. Determination of the sample based on the order of the population plants that have been numbered, this selection technique uses the principle of proportional sampling (systematic proportional sampling). While secondary data is obtained through the activities of collecting existing data or documents from both the library and information obtained from relevant institutions in the research needs and conducting literature studies.Based on the results of the study, it was found that the increments of Aquilaria microcarpa and Aquilaria beccariana species at the Arboretum of the Dipterocarpa Forest Ecosystem Research and Development Center in Samarinda varied. Both types of plants both experience an increase in the number of increments in diameter, height and volume per year